(untitled) (Research, Society and Development, 2020)
The optimization of resources is imperative in civil construction, whose purpose it is related to the reduction of losses during the process, and the consequent increase in productivity. These factors are related to the efficiency of the built environment, where it highlights the thermal behavior. The present work aims to evaluate the thermal load of cooling and heating of four constructive models by means of computer simulation: one model built with masonry system of ceramic blocks and three models in Light Steel Frame (LSF), using different combinations of materials. The simulation, using Autodesk Revit® 2020 software, was carried out under climatic conditions in the city of Marabá-PA. The results obtained show a better thermal behavior in the LSF method with thermoacoustic tile, which would be able to provide better thermal comfort to users and enhance the energy efficiency of the building.